Effects of processing variables on iridescence in precooked beef - Wang, H.; Kropf, Donald H.; Hunt, Melvin C.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Beef semitendinosus (ST) muscles with injected water (3 or 10% of raw muscle weight) and phosphate (0.3%) were cooked to final internal temperatures of 130 (held at 130 for 121 min), 140 (held at 140 for 12 min), 145, or 155°1\ then sliced at 30, 45, 120, 130, or 145<>P by either a dull or a sharp slicer. Biceps femoris (BF) muscles had the same treatment but only at 3% water addition. Controls were uninjected muscles from the opposite side of the carcass. For ST muscles (all with 0.3% added phosphate), 3% added water resulted in less iridescence than controls and those containing 10% added water. Iridescence was also lowered by cooking to 130°F (held for 121 min), slicing at 30 ̊F or slicing with a dull slicer blade. Iridescence varied (P<.05) among muscles from different carcasses under the same cooking and slicing conditions. BF muscles had much less iridescence than ST muscles. Our results show that processing-cooking- slicing alterations can help reduce iridescence, especially for the ST (eye of round) muscle.
Keywords: Beef; Iridescence; Phosphate; Internal temperature; Cooking temperature; Slicing temperature; Slicer blade